al-’afā’ī wa-’l-’ālihah: ’al-siḥr wa-’l- ’ālilah al-sūriyyah fī ’usṭūrah ’ūgārītiyyah Hūrūn wa-’l-’afā’ī - Būrdruway, Bīyar
Pierre Bordreuil; Snakes and Deities: Magic and the Syrian Deities in the Ugaritic Myth ”Horon and the Snakes”; ersch. 1986?; in Arabic, translated and abridged by Baš?r Zuhd?.